Effect of Continuous Airway Pressure on Lung Function in Patients Undergoing Cardiopulmonary Bypass: An Observational Study - Panta, Sukirti Baba; Parajuli, Santosh; Amatya, Ashish Govind (Nepalese Respiratory Journal, 2025)
Background: Postoperative pulmonary dysfunction remains a common complication following cardiopulmonary bypass (CPB), with atelectasis and impaired oxygenation contributing to delayed recovery and increased morbidity. Objective: To evaluate the effect of applying 5 cm H2O continuous positive airway pressure (CPAP) during CPB on postoperative lung function in patients undergoing cardiac surgery. Methods: This prospective observational study included 70 adult patients undergoing elective cardiac surgery. Patients were divided into two groups: CPAP (n = 35), who received 5 cm H2O CPAP during CPB, and no-CPAP (n = 35). The primary outcomes were PaO2/FiO2 ratio and driving pressure measured at predefined perioperative time points. Secondary outcomes included duration of mechanical ventilation, ICU stay, and incidence of postoperative pulmonary complications. Results: No statistically significant differences were observed between the CPAP and no-CPAP groups in PaO2/FiO2 ratios or driving pressures at any time point (p > 0.05). Although the CPAP group showed a trend toward better oxygenation (e.g., post-CPB PaO2/FiO2: 286 ± 72 vs. 264 ± 68) and lower driving pressure (11.2 ± 2.1 vs. 11.8 ± 2.4 cmH2O), these differences were not clinically significant. Mechanical ventilation duration (median 350 vs. 330 minutes) and ICU stay (48 vs. 56 hours) were also comparable between groups. Conclusions: Intraoperative application of 5 cm H2O CPAP during CPB did not significantly improve postoperative pulmonary function in patients with preserved baseline lung function. While minor trends toward improved oxygenation and reduced driving pressure were observed, the lack of statistically or clinically significant benefits suggests that a driving pressure of 5 cm H2O may be insufficient. Further research is warranted to explore individualized CPAP titration or adjunctive strategies for optimizing perioperative respiratory care in cardiac surgery.